Medical residency in health administration and management in Peru: analysis of vacancies offered and curricular plans - Arce-Huamani, Miguel A. (2024)
Introduction. The lack of research in Health Administration and Management (AyGS) training, along with the need to improve residency programs, motivated this study. Objective. We described the availability of offered positions and curriculum plans for AyGS residency programs in Peru. Methods. Descriptive observational study. We reviewed the number of positions offered and awarded between 2013 and 2022 on the National Medical Residency Council (CONAREME) website. Additionally, we analyzed curriculum plans updated to 2022, identifying minimum achievements per academic year and comparing them with CONAREME standards. Results. Between 2013 and 2022, nine universities offered the AyGS residency program, with six located in Lima. The allocation of open vacancies showed a higher trend, reaching 100% in four of the ten years analyzed, while the highest allocation percentage for captive positions was 78%. Regarding the curriculum plans, six of the eight available in 2022 provided information on minimum achievements and described the courses that residents must take. Conclusion. There were no changes in the total number of positions offered for the AyGS program. Three universities in Lima concentrate more than 50% of the program offerings. The curriculum plans show similarities across the universities offering the program.